Effect of weighted jump warm-up on vertical jump in Division II female volleyball players - Deneke, N.; Sevene-Adams, P. G.; Berning, J. M.; Curtin, M.; Adams, K. J. (The Journal of Strength and Conditioning Research, 2010)
Dynamic warm-up strategies are designed to positively impact performance. Research suggests that warm-ups which elicit a post activation potentiation (PAP) effect via high intensity muscular contractions may increase performance in subsequent activities requiring strength and power. The purpose of this investigation was to determine if a functional, dynamic, volleyball specific warm-up that included weighted jumps would elicit a PAP effect and increase subsequent vertical jump height. Ten trained female Division II volleyball players participated (age = 19.8 + 1.8 yrs; mass = 71.7 + 9.7 kg; ht = 167.8 + 23.9 cm). Subjects were at week 6 of their off-season conditioning program. Besides volleyball specific strength and conditioning, per NCAA guidelines, each player accumulates 2 hrs/wk of individual volleyball practice during this time period. Two different warm-up conditions lasting ~ 5-7 minutes were individually employed at two different training sessions within one week. The first warm-up condition consisted of a functional, dynamic warm-up of light jogging, high knees, carioca, shuffling, ankle pops (all at 3 sets at 20 yds ea.), pogos (2 x 15 sec.), and tuck jumps (1 x 15 sec.). The second warm-up condition was identical to the first, except for the addition of 1 x 10 maximal vertical jumps with countermovement while wearing a weight vest loaded with 20% of their individual bodyweight. Starting at 4-minutes post warm-up in each condition, maximal vertical jump was assessed in two conditions: 1) 2-hand standing block vertical jump (SBVJ), and 2) 1-hand 3-step approach vertical jump (AVJ). Three trials per each condition were given, with 15 sec. rest intervals allowed between trials. The highest point touched on a vertical jump tester was recorded for each trial. The average of the three trials was used for data analysis. Paired Samples T-test was used to determine if there was a significant difference (p < 0.05) in vertical jump height (i.e., height touched) between the two conditions. The results of this study were mixed. No significant difference (p > 0.05) occurred in vertical jump height in the SBVJ condition between the two different warm-ups (262.1 vs. 263.0 cm, warm-up vs. warm-up with weight vest, respectively). However, the AVJ was significantly higher by 2.7 cm (p < 0.05; 275.1 vs. 277.8 cm) after the subjects added the weight vest to their warm-up routine. This study demonstrates that a functional, dynamic warm-up with the addition of weight jumps for 1 x 10 at 20% of bodyweight increases 3-step approach vertical jump ability in female collegiate volleyball players. However, no effect was seen in 2-hand standing block vertical jump ability. This may possibly be explained by the difference in the forces and energy involved during the stretch-shortening cycle in a 3-step approach vertical jump vs. a stationary standing block vertical jump. The coach may consider using a functional, dynamic, athletic warm-up that includes jumps with resistance to optimize performance in sports like volleyball where vertical jumps with an approach are key components of competition.